Messenger - Lowry, Lois. (Boston : Houghton Mifflin, 2004)
In this novel that unites characters from "The Giver" and "Gathering Blue," Matty, a young member of a utopian community that values honesty, conceals an emerging healing power that he cannot explain or understand.
hardcover: Boston : Houghton Mifflin Books for Children, 2004.
Keywords: Utopias -- Juvenile fiction; Community life -- Juvenile fiction; Healers -- Juvenile fiction; Utopias -- Fiction; Community life -- Fiction; Healers -- Fiction; Science fiction; Science fiction